Hamlet Youth Efforts to Build a Village in Kulon Progo - Kelik Endro Suryono; Aida Dewi; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The background of this research is community participation in efforts to build village potential starting from the hamlet. The problem formulation in this research is 1) What is the planning strategy for building the potential of Bendungan village starting from the hamlet? 2) What are the obstacles faced in the village development planning strategy from the Dusun Kuncen Wates District, Kulon Progo Regency? 3) What are the efforts to overcome obstacles in the planning strategy for developing Villages from Dusun? The research design that the authors use is a descriptive analysis research design. The primary data source is that there are 15 people who were interviewed. Data collection techniques in this study were library research, and field studies (observations and interviews). Data analysis techniques in this study were collecting observation and interview data, interpreting observation and interview data, describing observation and interview data to answer the research problem formulation and drawing conclusions from observation and interview data to answer the research problem formulation. Based on the results of the study that 1) The village development planning strategy starting from Kuncen Hamlet, Wates District, Kulon Progo Regency, in general, can be implemented, but there are still several indicators of implementation that are still not optimal, 2) lack of awareness that village potential can be explored can be more beneficial for welfare 3) The efforts made, namely inviting the community to be more active, providing understanding to the community, are still not being implemented by the Village Government.